Effect of graphene on thermal stability of tin selenide - Manal Alsalama (17316895) (2022)
The thermal stability of polycrystalline tin selenide (SnSe) is essential for its long-term applications. In this study, the thermo-mechanical stability of hot compacted polycrystalline SnSe and SnSe/graphene nanocomposite is evaluated. All samples were prepared using a combination of mechanical alloying and hot compaction under an argon atmosphere. A severe bloating behavior was observed in the pristine SnSe hot compacted disks after post densification annealing. Consequently, these disks exhibited volume expansion and a drop in density, resulting in the formation of pores and cracks within the sample, which significantly degraded the electrical performance with consecutive thermal cyclings. Interestingly, the bloating behavior was reduced upon the incorporation of graphene within the SnSe matrix. However, this reduction was limited to samples with a homogeneous distribution of graphene. Dilatometer measurements showed that the as-compacted SnSe/graphene nanoplatelets (GNPs) sample in which graphene was milled for 4 h exhibited less hysteresis than the pristine SnSe sample. Accordingly, the electrical performance of the SnSe/GNP samples was more stable than the pristine SnSe after consecutive thermal cycles. The obtained results indicate that homogeneously distributed graphene plays a significant role in improving the thermal stability of the SnSe-based nanocomposite. Other Information Published in: Journal of Materials Research and Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jmrt.2022.02.045